Hubungan Pola Asuh dengan Perilaku Bullying pada Remaja SMP Negeri 19 Kota Jambi - Mohd Syukri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The prevalence of bullying is estimated at 8 to 50% in several Asian, American and European countries (Soedjatmiko, 2013). The results of research conducted by the National Association of School Psychologist showed that more than 160,000 adolescents in the United States skipped school every day for fear of bullying (Sari, 2010). KPAI has identified 369 complaints related to bullying at school. Bullying can occur when a person experiences forms of harassment and humiliation that are systematic and convincing for a long period of time (9-16 days in a month), does not rule out the possibility of occurring at home due to inappropriate parenting. This study aims to determine the relationship between parenting and bullying behavior in school. Crossectional research design. The sample amounted to 100 people with proportional random sampling sampling techniques. The results showed that there was a significant relationship between parenting and bullying behavior (p value <0.05). Authoritarian and permissive parenting tend to have a greater tendency to bullying children.